PENGARUH PERSEPSI KEMUDAHAN DAN FITUR LAYANAN TERHADAP MINAT PESERTA MENGGUNAKAN APLIKASI MOBILE JKN - Retno Dewi Wijiastuti; Eka Nur Fadhilah Febriyanti (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to determine the influence of perceived convenience and service features on participants' interest in using the Mobile JKN application which is limited to BPJS participants at the Sorong City Health Center. This research uses a quantitative approach with causal methods. The sample required in this research was 120 respondents with a sampling technique using nonprobability sampling and purposive sampling technique as a sample determination technique. The results of this research show that perceived convenience influences interest in using the Mobile JKN application with a tcount of 9.426 > ttable 1.980 and a significance value of 0.000, service features influence interest in using the Mobile JKN application with a tcount of 9.838 > ttable 1.980 and a significance value of 0.000. Together, perceptions of convenience and service features influence interest in using the Mobile JKN application with the result Fcount 65.535 > Ftable 3.07 and a significance value of 0.000.